Teachers' Conceptual Understanding of Learning Environments to Support Cognitive Development in Early Childhood Education: A Multi-Site Study - Subaita; Budiono; Husamah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Early childhood education (ECE) is fundamental for fostering lifelong learning and cognitive development, yet teachers’ varying conceptual understandings of learning environments can significantly shape children’s opportunities to explore, interact, and think critically. This multi-site qualitative study—the first within the Muhammadiyah Aisyiyah Kindergarten (TK ABA) network—analyzes variations in teachers’ perceptions and practices in designing learning environments that promote cognitive growth across three schools in Batu City, Indonesia. A qualitative descriptive approach was applied through classroom observations, in-depth interviews, and document analysis. Findings reveal distinct pedagogical orientations: TK ABA 01 demonstrated constructivist and inquiry-based practices with integrated loose parts; TK ABA 02 maintained conventional teacher-centered instruction; and TK ABA 03 reflected transitional patterns through exploratory outdoor learning with limited planning consistency. Quantitative descriptors supported these findings: planning quality (ABA01 = 4.6; ABA02 = 2.4; ABA03 = 3.8) and child engagement (ABA01 = 85%; ABA02 = 46%; ABA03 = 71%). These results underscore the centrality of environmental design, creative media use, and teacher collaboration in enhancing cognitive stimulation. The study offers novel insights into intra-network variations in early childhood pedagogy and recommends professional development that emphasizes ecological awareness and environment-based learning design to ensure equitable cognitive experiences for all children.